PENGARUH TARAF PENAMBAHAN TEPUNG KEDELAI SEBAGAI BAHAN PENGIKAT DAN METODE PEMASAKAN TERHADAP KADAR AIR DAN KADAR PROTEIN SOSIS AYAM - Efi Rokana; Mariatul Kholisyah (Jurnal Ilmiah Fillia Cendekia, 2017)
The aim of this reseach was to know the influence of soybean meal addition as a binder and cooking method to water content and protein content of chicken sausage. Variables in the study include: water content and protein levels in chicken sausage. The research method used was experimental using Factorial Random Design Randomized Design (RAL).The results showed that the average moisture content in the cooking method treatment from the smallest was the boiling method (66.27 ± 3.811) and the highest steaming method (68.93 ± 3.927), while the average protein content from the lowest was the steaming method (12.02 ± 1,058) and the highest method of boiling (13.68 ± 1.392). The average of water content in the treatment of soybean starch level from the lowest was 25% (62.36 ± 1.610), the level of 20% (68.23 ± 2.724), the level of 15% (68.85 ± 3.712), the highest was 0% (70.97 ± 1.282), while the average protein content from the lowest is 0% (11.88 ± 0.804), 15% (12.36 ± 0.690), 20% (12.99 ± 1.569), and the highest is 25% (14.16 ± 1.718).In conclusion of research, that the cooking method has a very significant effect on water content and chicken sausage protein level. The treatment of soybean starch level gave a very real effect to water content and protein content of chicken sausage. While the combination of treatment did not give effect to water content and protein content of chicken sausage.